2013
DOI: 10.1002/ajim.22180
|View full text |Cite
|
Sign up to set email alerts
|

Short, fine and WHO asbestos fibers in the lungs of quebec workers with an asbestos‐related disease

Abstract: Our findings stress the relevance of considering several dimensional criteria to characterize health risks associated with asbestos inhalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
(75 reference statements)
2
13
0
2
Order By: Relevance
“…Nevertheless, asbestos bodies were easily detectable in the lung dust analyses and histological evaluations (Figure 3a). This fact is confirmed by other authors [25][26][27] and in other studies [28]. Asbestos fibers, including chrysotile/white asbesbeen diagnosed as a bridge finding for BK 4104, recognition as an occupational disease had been recommended and this would not have been possible without the quite demanding lung dust analysis and histological examination applying iron staining.…”
Section: Discussionsupporting
confidence: 61%
“…Nevertheless, asbestos bodies were easily detectable in the lung dust analyses and histological evaluations (Figure 3a). This fact is confirmed by other authors [25][26][27] and in other studies [28]. Asbestos fibers, including chrysotile/white asbesbeen diagnosed as a bridge finding for BK 4104, recognition as an occupational disease had been recommended and this would not have been possible without the quite demanding lung dust analysis and histological examination applying iron staining.…”
Section: Discussionsupporting
confidence: 61%
“…Adib and colleagues analysed the fibres detected in lung tissue obtained from workers in Quebec whose disease was recognised as asbestos-related. The results showed that half of the asbestos fibres found in the lung tissues of workers were short (<5 µm) and the aspect ratios of the tremolite fibres were always <20:1 49. Some may suppose that short fibres are generated from the disintegration of long fibres; however, in an animal study conducted by Pott and colleagues, chrysotile asbestos was milled into short fibres, such that nearly 100% of the fibres were shorter than 5 µm, and were intraperitoneally injected into Wistar rats.…”
Section: Discussionmentioning
confidence: 97%
“…Even many years after the last exposure, asbestos fibres can be found in the lungs of asbestos worker. In a study of workers in Quebec, Canada, based on data collected between 1988-2007, even 30 years or more after the last exposure, chrysotile fibres were found in worker's lungs [29]. In North Carolina, USA, more than half of hospitalizations concerned persons aged 65-84 years [3].…”
Section: Discussionmentioning
confidence: 99%